Mixed-methods formative evaluation of implementing an adapted suicide prevention treatment: Dialectical Behavior Therapy Skills Groups in the Veterans Health Administration - Decker, Suzanne E.; Kroll-Desrosiers, Aimee; Mattocks, Kristin; Aunon, Frances M.; Galliford, Elizabeth; Doran, Neal; Baird, Scarlett; Rielage, Jennifer K.; Ridley, Josephine; Bannister, Jenny; Giovannelli, Thorayya S.; Landes, Sara J.; et al. (Frontiers in Psychiatry, 2024)
BackgroundPreventing veteran suicide requires addressing mechanisms driving suicidal behavior, such as emotion dysregulation. Dialectical Behavior Therapy Skills Groups (DBT-SG) are well established for reducing emotion dysregulation, improving coping skills, and in some studies, reducing suicide attempt, but will require implementation support to deliver DBT-SG and to test its effectiveness within the Veterans Health Administration (VHA).MethodsWe conducted a mixed-method developmental formative evaluation of DBT-SG at four VHA medical centers, guided by the Integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework, as part of a hybrid effectiveness-implementation trial (Clinical trials ID, NCT05000749).ResultsQuantitative Organizational Reasons for Change Assessment data (n = 30 VHA staff) and qualitative data (n = 35 VHA staff) were merged, compared, and triangulated. Quantitative and qualitative data largely converged, showing favorable views of evidence supporting DBT-SG and strong enthusiasm for its potential to reduce veteran suicide attempt. Staff noted DBT-SG’s broad applicability to veterans. Staff were less optimistic about the inner context supporting DBT-SG implementation, commenting on how limited staffing could be a barrier despite leadership wanting to support suicide prevention.ConclusionsImplementation barriers to DBT-SG at VHA include limited staffing, despite staff enthusiasm. The next phase of this project will evaluate DBT-SG effectiveness in a randomized controlled trial.Clinical trials registrationhttps://clinicaltrials.gov/study/NCT05000749, identifier NCT05000749.